2022
DOI: 10.1111/jocn.16193
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and risk factors of nasal mucosal pressure injury in intensive care units

Abstract: Aims and Objectives This study aimed to understand the risk factors that contribute to medical device‐related (MDR) nasal mucosal membrane pressure injuries (MM PI) in ICU patients. Background ICU patients require substantial tube‐based life support such as oxygen tubes, tracheal intubation and indwelling gastric tubes. As a result, there is an increased risk of PI occurrence; however, few studies have assessed the risk factors associated with nasal mucosal MDR‐MMPI in ICU patients. Design A cross‐sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…This study showed that a high APACHE-II score was a significant difference between the FPI group and the non-FPI group. Previous studies found that high APACHE-II scores were a contributing factor to medical device-related pressure injury (MDRPI) (Cox & Schallom, 2021;Nan et al, 2022), which was consistent with this study. Nan et al (2022) showed that MDRPI patients in the ICU were positively associated with high APACHE-II scores.…”
Section: Patients With Higher Apache-ii Scores Were More Likely To De...supporting
confidence: 92%
See 3 more Smart Citations
“…This study showed that a high APACHE-II score was a significant difference between the FPI group and the non-FPI group. Previous studies found that high APACHE-II scores were a contributing factor to medical device-related pressure injury (MDRPI) (Cox & Schallom, 2021;Nan et al, 2022), which was consistent with this study. Nan et al (2022) showed that MDRPI patients in the ICU were positively associated with high APACHE-II scores.…”
Section: Patients With Higher Apache-ii Scores Were More Likely To De...supporting
confidence: 92%
“…Previous studies found that high APACHE-II scores were a contributing factor to medical device-related pressure injury (MDRPI) (Cox & Schallom, 2021;Nan et al, 2022), which was consistent with this study. Nan et al (2022) showed that MDRPI patients in the ICU were positively associated with high APACHE-II scores. Thus, higher APACHE-II scores (meaning severe disease state) highlight detrimental changes in patient hemodynamic instability and the potential to worsen dynamic physiologic parameters (Cox & Schallom, 2021).…”
Section: Patients With Higher Apache-ii Scores Were More Likely To De...supporting
confidence: 92%
See 2 more Smart Citations
“…The shape of the injury is often consistent with the shape of the medical devices. The prevalence of MDRPI in critically ill patients in the intensive care unit (ICU) is due to the frequent use of various medical devices, extensive drug therapy and patients' own characteristics such as skin edema 7‐10 . It is now one of the more serious adverse events in ICU patients 11,12 .…”
Section: Introductionmentioning
confidence: 99%